THE MULTIPLE ROLE OF WOMAN, COPING STRATEGY, AND FAMILY RESILIENCE DURING COVID-19 PANDEMIC - Marelina Indrastuti; Tin Herawati (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2023)
The Covid-19 pandemic has disrupted family life mechanisms, especially families with multiple roles of women. The purpose of this study is to analyze women's dual roles, coping strategies, and family resilience during the Covid-19 pandemic. This study involved 100 mothers working in the formal sector who have school-age children (elementary school). The research location is in the Bogor Regency area, West Java. Sampling was conducted by non-probability sampling using voluntary sampling technique. The data obtained were then processed using Microsoft Office Excel 2010 software and analyzed using the Statistical Package for Social Science (SPSS) 25 program. Data processing was carried out using descriptive analysis, correlation analysis, and regression analysis. The results showed that there was a significant relationship between family characteristics, women's dual roles, coping strategies, and family resilience. The regression test results show that women's dual roles have a positive effect on family resilience. It is expected that families with dual roles of women can increase their contribution in the public environment through various activities such as PKK (Family Welfare Development), committees for celebrating holidays, community organizations and others. further research is expected to examine the dual role of women through two perspectives, namely the husband's side and the wife's side so that the data produced is more accurate.